Cerebrospinal fluid neurofilament light chain levels predict visual outcome after optic neuritis. (April 2016) - Modvig, S; Degn, M; Sander, B; Horwitz, H; Wanscher, B; Sellebjerg, F; Frederiksen, JL
Background: Optic neuritis is a good model for multiple sclerosis relapse, but currently no tests can accurately predict visual outcome. Objective: The purpose of this study was to examine whether cerebrospinal fluid (CSF) biomarkers of tissue damage and remodelling (neurofilament light chain (NF-L), myelin basic protein, osteopontin and chitinase-3-like-1) predict visual outcome after optic neuritis. Methods: We included 47 patients with optic neuritis as a first demyelinating episode. Patients underwent visual tests, optical coherence tomography (OCT), magnetic resonance imaging (MRI) and lumbar puncture. Biomarkers were measured in CSF by enzyme-linked immunosorbent assay (ELISA). Patients were followed up six months after onset and this included visual tests and OCT. Outcome measures were inter-ocular differences in low contrast visual acuity (LCVA), retinal nerve fibre layer (RNFL) and ganglion cell layer+inner plexiform layer (GC-IPL) thicknesses. Results: CSF NF-L levels at onset predicted inter-ocular differences in follow-up LCVA (β=13.8, p =0.0008), RNFL (β=5.6, p =0.0004) and GC-IPL (β=4.0, p =0.0008). The acute-phase GC-IPL thickness also predicted follow-up LCVA (β=12.9, p =0.0021 for NF-L, β=−1.1, p =0.0150 for GC-IPL). Complete/incomplete remission was determined based on LCVA from 30 healthy controls. NF-L had a positive predictive value of 91% and an area under the curve (AUC) of 0.79 for incomplete remission. Conclusion: CSF NF-L is a promising biomarker of visual outcome after optic neuritis. This could aid neuroprotective/regenerative medical advancements.